Labor Supply Shocks and Capital Accumulation: The Short and Long Run Effects of the Refugee Crisis in Europe - Lorenzo Caliendo; Luca David Opromolla; Fernando Parro; Alessandro Sforza (Center for Economic Studies and ifo Institute (CESifo), 2023)
European countries experienced a large increase in labor supply due to the influx of Ukrainian refugees after the 2022 Russia invasion. We study its dynamic effects in a spatial model with forward-looking households of different skills, trade, and endogenous capital accumulation. We find that real GDP increases in Europe in the long term, with large distributional effects across countries and skill groups. In the short run, an increase in the supply of labor strains the use of capital structures that takes time to build. Over time, countries that build capital structures increase output, resulting in potential long run benefits.
Keywords: 330; Arbeitsangebot; Flüchtlinge; Ukrainer; Investition; Bruttoinlandsprodukt; Wohlfahrtsanalyse; Verteilungswirkung; Europa